2013
DOI: 10.1371/journal.pone.0056518
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Germline Competent Transgenic Fischer 344 Embryonic Stem Cell Line

Abstract: Embryonic stem (ES) cell-based gene manipulation is an effective method for the generation of mutant animal models in mice and rats. Availability of germline-competent ES cell lines from inbred rat strains would allow for creation of new genetically modified models in the desired genetic background. Fischer344 (F344) males carrying an enhanced green fluorescence protein (EGFP) transgene were used as the founder animals for the derivation of ES cell lines. After establishment of ES cell lines, rigorous quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In our study, the frequency of both Leptin and p53 gene targeting via homologous recombination was 20% with SD and F344 ES cells, in comparison with previously reported typical efficiencies of 0.6-4.4% [27,34]. Although germline-competent rat ES cells have been derived from various strains [1,2,23,35], the knockout rats generated via homologous recombination have only been achieved in DA rats [27,32,34]. It has also been reported that the gene targeting event resulted in the failure of germline transmission in SD rat ES cells [32].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In our study, the frequency of both Leptin and p53 gene targeting via homologous recombination was 20% with SD and F344 ES cells, in comparison with previously reported typical efficiencies of 0.6-4.4% [27,34]. Although germline-competent rat ES cells have been derived from various strains [1,2,23,35], the knockout rats generated via homologous recombination have only been achieved in DA rats [27,32,34]. It has also been reported that the gene targeting event resulted in the failure of germline transmission in SD rat ES cells [32].…”
Section: Discussionsupporting
confidence: 68%
“…Although germline‐competent rat ES cells have been derived from various strains 1, 2, 23, 35, the knockout rats generated via homologous recombination have only been achieved in DA rats 27, 32, 34. It has also been reported that the gene targeting event resulted in the failure of germline transmission in SD rat ES cells 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering the above limitations in efficiency, size of engineered knockins, and potential for intellectual property issues and scalability, the rat ESC still promises to have a significant and important role in the full potential of the rat model for CVD research. First established in 2008, authentic germline-competent rat ESC have now been derived from a few inbred, outbred, and hybrid strains, including Dark Agouti, Fisher F344, and Sprague Dawley [40, 45, 7476]. These cell lines are also currently available through the RRRC.…”
Section: Choosing and Implementing The Methodology For Genetically Momentioning
confidence: 99%
“…We carried out electroejaculation and semen collection for 11 male chimeric rats derived from injection of F344-Tg.EC4011/Rrrc ESCs (Rat Resource and Research Center RRRC# 654, Columbia, MO) into dark agouti × Sprague-Dawley blastocysts 7 . Rats were approximately 9–10 months of age.…”
Section: Procedural Success Ratementioning
confidence: 99%